GEN Z JOB SEEKERS' INTENTION TOWARDS E-RECRUITMENT IN CENTRAL KALIMANTAN TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH - Panjaitan, Olivia Winda Ony; Trecy Anden; Anike Retawati (ZILLZELL MEDIA PRIMA, 2023)
This study aims to analyze job seekers' interest in using E-recruitment with the Technology Acceptance Model (TAM) approach. Research data were obtained through an online questionnaire. The sampling technique used purposive sampling technique. Respondents in this study were individuals born between 1995 - 2010. The sample size was 82 respondents who were e-recruitment users. Data were analyzed with PLS-SEM. This study found that the E-recruitment system is very attractive to Gen-Z to find information about the jobs they want. The results of the study prove that perceived ease of use, perceived usefulness and attitude towards using have a positive and significant effect on behavioral intention to use the E-recruitment system on Gen-Z respondents.